The unrevealed potential of elemental sulfur for the synthesis of high sulfur content bio-based aliphatic polyesters. Issue 2 (15th October 2019) - Duarte, Martín E.; Huber, Birgit; Theato, Patrick; Mutlu, Hatice
Abstract : We introduce a novel sulfur-containing polyester derivative based on a renewable monomer bearing secondary disulfide groups. Base-mediated sulfur exchange reaction of disulfide bonds using S8 delivers polyesters with tailored functional properties. Abstract : We introduce a novel sulfur-containing polyester derivative based on a renewable monomer bearing secondary disulfide groups. Specifically, we demonstrate that this secondary disulfide moiety, placed in each repeating unit within the polymer, enables the introduction of high sulfur content by virtue of an organocatalytically triggered sulfur exchange reaction using elemental sulfur, thereby facilitating the synthesis of sustainable aliphatic polyesters with tailored functional properties.